Bedside Monitoring to Adjust Antiplatelet Therapy for Coronary Stenting - Collet, Jean-Philippe; Cuisset, Thomas; Rangé, Grégoire; Cayla, Guillaume; Elhadad, Simon; Pouillot, Christophe; Henry, Patrick; Motreff, Pascal; Carrié, Didier; Boueri, Ziad; Belle, Loic; Van Belle, Eric; et al. (The New England journal of medicine, 2012)
In this trial, bedside platelet-function monitoring to adjust antiplatelet therapy after coronary stent implantation did not reduce the rate of subsequent cardiovascular events, a finding that calls into question the clinical value of this type of testing. Clopidogrel and aspirin play a central role in the treatment of patients undergoing percutaneous coronary intervention. 1 Up to one third of patients have inadequate platelet inhibition, with an increased risk of events. 2 – 5 Platelet-function testing can determine the degree of platelet reactivity during treatment at the bedside and potentially identify patients in whom adjustment of antiplatelet therapy is warranted to minimize the risks of both ischemic and bleeding complications. 6 Cohort studies and meta-analyses have largely shown the prognostic value of high platelet reactivity during antiplatelet therapy in patients undergoing coronary stenting. 7 , 8 Randomized clinical trials have also shown that stronger . . .